2019
DOI: 10.3389/fnint.2019.00058
|View full text |Cite
|
Sign up to set email alerts
|

Mild Mechanic Stimulate on Acupoints Regulation of CGRP-Positive Cells and Microglia Morphology in Spinal Cord of Sciatic Nerve Injured Rats

Abstract: ObjectiveThe objective of this study is to observe the effects of mild mechanical stimulation on acupuncture points of spinal motor neurons and active substances of sciatic nerve injury in rats, and to explore the morphological basis for the recovery of motor function in rats with sciatic nerve injury, using mild acupuncture. Acupuncture in the local area of injury may cause further damage to the peripheral nerve injury. We believe that mild mechanical stimulation on the surface, using some specific acupunctur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 26 publications
0
8
0
Order By: Relevance
“…CGRP operates via its receptor that, in many cell types, leads to a range of biological effects including those associated with neurons and microglia [ 6 , 7 ]. A functional CGRP receptor consist of 3 components, the calcitonin receptor-like receptor (CRLR), receptor activity-modifying protein 1 (RAMP1), and CGRP receptor component protein (CRCP) that couple the receptor to the cellular signal pathway leading to increased intracellular cAMP and activated protein kinase A (PKA) [ 8 ].…”
Section: Introductionmentioning
confidence: 99%
“…CGRP operates via its receptor that, in many cell types, leads to a range of biological effects including those associated with neurons and microglia [ 6 , 7 ]. A functional CGRP receptor consist of 3 components, the calcitonin receptor-like receptor (CRLR), receptor activity-modifying protein 1 (RAMP1), and CGRP receptor component protein (CRCP) that couple the receptor to the cellular signal pathway leading to increased intracellular cAMP and activated protein kinase A (PKA) [ 8 ].…”
Section: Introductionmentioning
confidence: 99%
“…As a sensitive bio-marker, CGRP expresses on the sensory nerve fibers that are widely distributed in the skin and visceral tissues (Eftekhari et al, 2013 ; Carr and Frings, 2019 ; Li et al, 2019 ; Smolilo et al, 2020 ). Previous studies have shown that CGRP-positive nerve fibers originate from the sensory neurons in DRGs and distribute widely in the local skin tissues of acupoints and the visceral tissues (Ha et al, 2014 ; Fan et al, 2018 ; De Logu et al, 2019 ).…”
Section: Discussionmentioning
confidence: 99%
“…Rats were subjected to fasting and water prohibition for 24°h before the surgery [15] and were anesthetized by intraperitoneal injection of 1% pentobarbital sodium (0.35 mL/100 g).…”
Section: Animals and Modeling Methods Forty-five Male Spraguementioning
confidence: 99%
“…Tuina can promote the regeneration of the myelin sheath and axons of the sciatic nerve fiber in SNI rats, alleviate the edema of Schwann cell cytoplasm and mitochondria, and promote the repair and regeneration of the injured nerve ultrastructure [13]. Tuina can improve the behavioral indexes of SNI rats, promote the expression of neurotrophic factors (NTFS), protect neurons, prevent muscle atrophy, and significantly promote the recovery of SNI [14,15]. RNA-sequencing (RNA-seq) is a technique for sequence detection from transcriptional information formed into the transcription process of specific tissues and cell types.…”
Section: Introductionmentioning
confidence: 99%